2013
DOI: 10.1249/mss.0b013e318292c0ec
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Energy Cost of Running during a 24-h Treadmill Exercise

Abstract: The present study characterized accurately the changes of energy cost and substrate use during an extreme run, showing a plateau after 8 h of exercise. It is also concluded that the participants who maintained the highest %VV˙O2max were also those having most deteriorated their Cr over the 24TR, supporting the notion of a trade-off between running speed (relative to VV˙O2max) and Cr.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 25 publications
9
58
0
2
Order By: Relevance
“…Considering previously published literature, we could speculate a role of fatigue in determining a reverse J-shaped pacing strategy 1,2,26 . In 24-h race simulations on a treadmill, speed declined regularly from the beginning until 16 h (similar to our study) and remained constant afterwards (different) 23,24 . Martin et al 23 showed a large maximal muscle torque reduction after the 24-h trial and an increase in ratings of perceived exertion (RPE)-from the beginning until 16 h, tending to plateau around 15 points afterwards.…”
Section: General Pacing Strategy and Performance Group Differencessupporting
confidence: 86%
“…Considering previously published literature, we could speculate a role of fatigue in determining a reverse J-shaped pacing strategy 1,2,26 . In 24-h race simulations on a treadmill, speed declined regularly from the beginning until 16 h (similar to our study) and remained constant afterwards (different) 23,24 . Martin et al 23 showed a large maximal muscle torque reduction after the 24-h trial and an increase in ratings of perceived exertion (RPE)-from the beginning until 16 h, tending to plateau around 15 points afterwards.…”
Section: General Pacing Strategy and Performance Group Differencessupporting
confidence: 86%
“…Davies and Thompson (Davies and Thompson, 1986) observed a linear increase of V · O2,max with time from the 50th to 240th minute during a 4 h race on a treadmill at constant speed, the rise becoming significant (P<0.01) after 110 min of exercise. In addition, the ability to maintain a high F over a 24 h treadmill run was found to be mainly related to a low CoT (Gimenez et al, 2013;Millet et al, 2011), and in the same study participants a significant change in running biomechanics, including higher oscillation frequency, lower vertical stiffness and lower ground reaction force (GRF), was observed . Indeed, interventions to reduce CoT are constantly sought by athletes, coaches and sport scientists.…”
Section: Introductionmentioning
confidence: 73%
“…It should also be noted that, whereas lowering step frequency would be beneficial in terms of lowering CoT (Gimenez et al, 2013;Morin et al, 2011), it might also cause greater muscular damage, which could have negative consequences in long races (Millet et al, 2012).…”
Section: Factors Determining Performancementioning
confidence: 99%
“…Durante o cardiovascular drift, participantes de exercício físico aeróbico, podem reduzir o ritmo de trabalho físico, a fim de manter constante a FC dentro da zona alvo de treinamento pré-estabelecido, podendo resultar em esforço físico abaixo do pretendido em termos de intensidade 18 . O aumento da produção de calor, juntamente com a dificuldade de dissipar, pode promover aumentos na temperatura interna corporal pelos seus efeitos sobre o sistema nervoso central, que limita a capacidade de continuar o exercício 40 . Se o exercício é de longa duração e os líquidos perdidos através do suor não forem repostos, a desidratação resultante põe em jogo problemas de controle cardiovasculares 40 .…”
Section: Discussionunclassified
“…O aumento da produção de calor, juntamente com a dificuldade de dissipar, pode promover aumentos na temperatura interna corporal pelos seus efeitos sobre o sistema nervoso central, que limita a capacidade de continuar o exercício 40 . Se o exercício é de longa duração e os líquidos perdidos através do suor não forem repostos, a desidratação resultante põe em jogo problemas de controle cardiovasculares 40 . O exercício realizado no calor de forma independente ou combinando os efeitos do estresse em ambiente quente com a desidratação, podem mudar os limites da regulação da temperatura corporal e gerar prejuízos a desempenho, afetando mecanismos relacionados ao SNC, metabolismo ou sistema cardiovascular 41 .…”
Section: Discussionunclassified